Size-Selected Ag Nanoparticles with Five-Fold Symmetry - Gracia Pinilla, Miguel Ángel; Ferrer, Domingo A.; Mejía Rosales, Sergio; Pérez Tijerina, Eduardo (Springer, 2009)
Silver nanoparticles were synthesized using the inert gas aggregation technique. We found the optimal experimental conditions to synthesize nanoparticles at different sizes: 1.3 ± 0.2, 1.7 ± 0.3, 2.5 ± 0.4, 3.7 ± 0.4, 4.5 ± 0.9, and 5.5 ± 0.3 nm. We were able to investigate the dependence of the size of the nanoparticles on the synthesis parameters. Our data suggest that the aggregation of clusters (dimers, trimer, etc.) into the active zone of the nanocluster source is the predominant physical mechanism for the formation of the nanoparticles. Our experiments were carried out in conditions that kept the density of nanoparticles low, and the formation of larges nanoparticles by coalescence processes was avoided. In order to preserve the structural and morphological properties, the impact energy of the clusters landing into the substrate was controlled, such that the acceleration energy of the nanoparticles was around 0.1 eV/atom, assuring a soft landing deposition. High-resolution transmission electron microscopy images showed that the nanoparticles were icosahedral in shape, preferentially oriented with a five-fold axis perpendicular to the substrate surface. Our results show that the synthesis by inert gas aggregation technique is a very promising alternative to produce metal nanoparticles when the control of both size and shape are critical for the development of practical applications.